1975
DOI: 10.1111/j.1365-2222.1975.tb01838.x
|View full text |Cite
|
Sign up to set email alerts
|

Ragweed hay fever: treatment by local passive administration of IgG antibody

Abstract: Summary To determine whether the local administration of IgG antibodies might reduce the symptoms of ragweed hay fever, we tested the effect of this treatment in fourteen patients in a double‐blind pilot trial. The patients were randomly divided into two groups, treatment and placebo, and their symptoms and medication usage were determined during the ragweed pollination season. One group used a nasal spray consisting of phosphate‐buffered saline (PBS) containing human serum albumin, whereas the other used PBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The anti-SARS-CoV-2 RBD IgY was designed to capture and immobilize SARS-CoV-2 on the nasal mucosa, preventing the virus from binding to and spreading across the nasal mucosa, and also preventing the transmission of the virus to other individuals. Intranasal delivery of mammalian immunoglobulins as antiviral agents has been extensively evaluated in humans ( 49 54 ). Human immunoglobulins G (IgG) and A given intranasally are well tolerated ( 49 54 ), including in pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-SARS-CoV-2 RBD IgY was designed to capture and immobilize SARS-CoV-2 on the nasal mucosa, preventing the virus from binding to and spreading across the nasal mucosa, and also preventing the transmission of the virus to other individuals. Intranasal delivery of mammalian immunoglobulins as antiviral agents has been extensively evaluated in humans ( 49 54 ). Human immunoglobulins G (IgG) and A given intranasally are well tolerated ( 49 54 ), including in pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…That nasal ab would be more effective in controlling hay fever was also suggested by the report (35) that autologous serum-blocking ab applied locally in the nose will reduce symptoms. However, more recent attempts to confirm this finding were not successful (36). The present study was designed to investigate the role of nasal ab in hay fever and the possible relevance of nasal immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Purified IgG from a patient with a high titer of specific IgG was administered by nasal spray, and the patients were then observed during challenge or during the pollen season. One study showed an effect of passive administration of IgG, the results of which could, however, not be reproduced in another study [120, 121]. In bee-venom-allergic patients, intravenous or intramuscular administration of plasma from hyperimmune beekeepers with high levels of specific IgG had a protective effect in a following allergen challenge [122, 123].…”
Section: Therapeutic Use Of Blocking Antibodies: Can Polyclonal Blockmentioning
confidence: 99%